Prevalence of neurodevelopmental disorders among US children and adolescents in 2019 and 2020 - Yang, Yiwei; Zhao, Shi; Zhang, Meihui; Xiang, Mi; Zhao, Jian; Chen, Shucheng; Wang, Hui; Han, Lefei; Ran, Jinjun (Frontiers in Psychology, 2022)
Background: Concerning the changes in the prevalence of neurodevelopmental disorders (NDDs), we estimate the prevalence of attention-deficit/hyperactivity disorder (ADHD), autism spectrum disorder (ASD), intellectual disorder (ID), learning disability (LD) among US children and adolescents aged 3-17 years in 2019-2020. Methods: The study includes 14,983 US children and adolescents aged 3-17 years in 2019-2020 from the National Health Interview Survey (NHIS). Parents were interviewed about whether their children ever and/or currently had NDDs diagnosed. Prevalence estimates of NDDs were calculated with a survey-based weighting scheme. Logistic regression models were used to estimate the associations between NDDs prevalence and subgroups. Results: The weighted prevalence of ADHD, ASD, ID and LD were 8.5% (95%CI: 7.9%–9.2%), 2.9% (95%CI: 2.6%–3.4%), 1.4% (95%CI: 1.2%–1.7%), and 6.4% (95%CI: 5.8%–7.0%), respectively. Higher prevalence of ADHD, ASD, ID and LD were observed in boys, those who ever had anxiety or depression symptoms, those with lower family income, those living in a rented house, ever been bullied and ever lived with anyone mentally ill. Conclusions: The study found the prevalence of ADHD, ASD, ID and LD were different by demographics, comorbidity/mental problems, household/parental characteristics, and stressful life events.